Renewing U.S. telecommunications research - Lucky, R. W.; Eisenberg, Jon (National Academies Press, 2006)
The modern telecommunications infrastructure made possible by research performed over the last several decades is an essential element of the U.S. economy. The U.S. position as a leader in telecommunications technology, however, is at risk because of the recent decline in domestic support of long-term, fundamental telecommunications research. To help understand this challenge, the National Science Foundation asked the NRC to assess the state of telecommunications research in the United States and recommend ways to halt the research decline. This report provides an examination of telecommunications research support levels, focus, and time horizon in industry, an assessment of university telecommunications research, and the implications of these findings on the health of the sector. Finally, it presents recommendations for enhancing U.S. telecommunications research efforts.